Factors affecting the non-ownership of later in the family in Asuhan Kelahan Siantar Timur Pematangsiantar - Ismi Noer Fadilah; Putri Permata Sari (Science Midwifery, 2022)
The family does not own a latrine because they do not have the costs to build a latrine and because the ownership status of the house is not their own. This type of research is descriptive with the location of the research being conducted in the Asuhan Subdistrict of Siantar Timur Pematangsiantar District in 2016 which was carried out July-September 2016. The population in this study were all heads of families who did not have latrines in the Asuhan Subdistrict of Siantar Timur Pematangsiantar District in 2016, namely 31 families and a population is sampled. The results showed that the majority had junior high school education, namely 11 people (35.5%) and high school, namely 11 people (35.5), while the minority had the last elementary education, namely 3 people (9.7%). The majority have jobs as private employees, namely 12 people (38.7%), while the minority do not work, namely 3 people (9.7%). The majority have income > 1,000,000, namely 19 people (61.3%) while the minority have income > 1,000,000, namely 12 people (38.7%). The majority have less knowledge, namely as many as 16 people (51.6%) while the minority have good knowledge, namely as many as 15 people (48.4%). As the head of the family must be more concerned about basic sanitation health because it is important in maintaining a healthy environment to prevent disease and its transmission. The Puskesmas must conduct a latrine ownership screening and provide appropriate counseling for families. For kelurahans to be able to invite and provide understanding to their citizens the importance of maintaining environmental health for the common good. This research can be used to develop community knowledge so that awareness grows to have a latrine and provide direct experience in carrying out research, writing research results and adding insight and provision of knowledge in work in society